1997
DOI: 10.1063/1.475234
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and dynamics of superexcited states of diatomic molecules: General theoretical procedure

Abstract: Articles you may be interested inAb initio interatomic decay widths of excited states by applying Stieltjes imaging to Lanczos pseudospectra J. Chem. Phys. 134, 094107 (2011); 10.1063/1.3558739Single-photon spectroscopy of singlet sulfur atoms and the autoionization lifetime measurements of the superexcited singlet states A theoretical simulation of the 1s→2π excitation and deexcitation spectra of the NO molecule A general theoretical procedure to analyze the characteristics and dynamics of superexcited states… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
4
8
0
Order By: Relevance
“…From experimental data, the model found the outer hump in the D′ state to be between 0.106 and 0.1588 eV above the asymptote compared to the value found here of 0.167 eV. The ab initio calculation showed the 2 1 Π curve crossing the ion at the outer turning point of v = 0 in agreement with the result reported here (but slightly to smaller R ).…”
Section: Comparison To Prior Researchsupporting
confidence: 87%
See 2 more Smart Citations
“…From experimental data, the model found the outer hump in the D′ state to be between 0.106 and 0.1588 eV above the asymptote compared to the value found here of 0.167 eV. The ab initio calculation showed the 2 1 Π curve crossing the ion at the outer turning point of v = 0 in agreement with the result reported here (but slightly to smaller R ).…”
Section: Comparison To Prior Researchsupporting
confidence: 87%
“…The results reported here (see Figure ) show that the crossing occurs near the large R turning point of v = 0, in agreement with the model potential (but slightly to smaller R ) and in clear disagreement with the ab initio result. The ab initio calculation also does not display a hump for R < 4 Å and is purely repulsive in disagreement with the results reported here. From experimental data, the model found the outer hump in the D′ state to be between 0.106 and 0.1588 eV above the asymptote compared to the value found here of 0.167 eV.…”
Section: Comparison To Prior Researchsupporting
confidence: 81%
See 1 more Smart Citation
“…Possibly the continuum of the bound A 1 ⌸ state plays a role as well. After an ab initio calculation, Hiyama et al 38 shifted the absolute energy of the repulsive 1 ⌸ potential somewhat, based on a comparison with experimental findings of Komatsu et al 42 The dissociative 1 ⌸ state indeed crosses the E-state potential; further calculations on the crossing between these states may establish the predissociation rates and values for ⌫ E , including their isotope dependence, as found in the present study. These calculations should also reproduce the larger rate of predissociation in the E 1 ⌸, vϭ2 state and the smaller rate for E 1 ⌸, vϭ0.…”
Section: Discussionsupporting
confidence: 69%
“…The origin of the overall predissociation of each of the two states is less well understood. Ab initio quantum chemical calculations on the excited state potentials of CO, including the dissociative ones, have been performed by O'Neil and Schaefer 18 and more recently by Hiyama et al 37,38 Two repulsive singlet states are clearly identified in the calculations, one of 1 ⌺ ϩ and one of 1 ⌸ symmetry. The 1 ⌺ ϩ state even supports some bound levels at lower excitation energies and at large bond lengths; these levels were observed by Wolk and Rich, 39 who termed this state as D' 1 ⌺ ϩ .…”
Section: Discussionmentioning
confidence: 99%